2021
DOI: 10.1088/1757-899x/1047/1/012178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vibration treatment during welding on technological strength of chromium martensitic steel P91

Abstract: The paper shows the possibility of using the technology of vibration treatment in the process of welding of high-temperature chromium steel of martensitic class P91 applied to the product to increase the technological strength of welded joints and the effect of this technology on mechanical properties before and after thermal treatment. Application of vibration action on welding bath and weld seam in process of manufacturing of welded structure may allow to reduce inhomogeneity of weld metal structure in liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Optimum parameters of 9% nickel steel are achieved by very precise temperature control during production and controlled quenching. Preheating is performed only if high humidity is condensed on parts or welding works are carried out at temperature below 5 ° C [1,[16][17][18][19].…”
Section: Investigation Of the Process Of Nickel Impact On Steelmentioning
confidence: 99%
“…Optimum parameters of 9% nickel steel are achieved by very precise temperature control during production and controlled quenching. Preheating is performed only if high humidity is condensed on parts or welding works are carried out at temperature below 5 ° C [1,[16][17][18][19].…”
Section: Investigation Of the Process Of Nickel Impact On Steelmentioning
confidence: 99%
“…However, in some specific cases, the small deformation caused by vibration can reduce the welding stress [8]. With the change of vibration mode and frequency, low-frequency vibration welding can improve the toughness of welded joints without negative impact on other mechanical properties [9]. It has also been reported that applying an electromagnetic field in the welding process can effectively refine the weld grains and improve the weld hardness but, unfortunately, will weaken some mechanical properties of the weld, including strength and toughness [10,11].…”
Section: Introductionmentioning
confidence: 99%